B1+ B_1^+ ‐correction of magnetization transfer saturation maps optimized for 7T postmortem MRI of the brain. Issue 4 (13th November 2022) - Lipp, Ilona; Kirilina, Evgeniya; Edwards, Luke J.; Pine, Kerrin J.; Jäger, Carsten; Gräßle, Tobias; ,; Weiskopf, Nikolaus; Helms, Gunther
Abstract : Purpose: Magnetization transfer saturation ( MTsat MTsat ) is a useful marker to probe tissue macromolecular content and myelination in the brain. The increased B 1 + B_1^+ ‐inhomogeneity at ≥ 7 7 T and significantly larger saturation pulse flip angles which are often used for postmortem studies exceed the limits where previous MTsat MTsat B 1 + B_1^+ correction methods are applicable. Here, we develop a calibration‐based correction model and procedure, and validate and evaluate it in postmortem 7T data of whole chimpanzee brains. Theory: The B 1 + B_1^+ dependence of MTsat MTsat was investigated by varying the off‐resonance saturation pulse flip angle. For the range of saturation pulse flip angles applied in typical experiments on postmortem tissue, the dependence was close to linear. A linear model with a single calibration constant C C is proposed to correct bias in MTsat MTsat by mapping it to the reference value of the saturation pulse flip angle. Methods: C C was estimated voxel‐wise in five postmortem chimpanzee brains. "Individual‐based global parameters" were obtained by calculating the mean C C within individual specimen brains and "group‐based global parameters" by calculating the means of the individual‐based global parameters across the five brains. Results: The linear calibration model described the data well, though C C was not entirely independent of the underlying tissue and B 1 + B_1^+ . Individual‐based correction parameters and a group‐based global correction parameter ( C = 1 . 2 C=1.2 ) led to visible, quantifiable reductions of B 1 + B_1^+ ‐biases in high‐resolution MTsat MTsat maps. Conclusion: The presented model and calibration approach effectively corrects for B 1 + B_1^+ inhomogeneities in postmortem 7T data.